2001
DOI: 10.1002/path.928
|View full text |Cite
|
Sign up to set email alerts
|

Loss of alveolar basement membrane type IV collagen α3, α4, and α5 chains in bronchioloalveolar carcinoma of the lung

Abstract: Type IV collagen, the major component of basement membrane (BM), is composed of six genetically distinct alpha(IV) chains. This study investigated for the first time the expression of these six alpha(IV) chains immunohistochemically, using alpha(IV) chain-specific monoclonal antibodies, in normal lung and in small (less than 2 cm in diameter) adenocarcinoma of the lung with a bronchioloalveolar growth pattern at the periphery. Small adenocarcinomas were histopathologically classified into three subtypes: bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…Similarly, we found that TGF-β1 stimulation, in a dose-dependent manner, increased the production and mRNA expression of α1(IV) and α2(IV) chains, but not α3(IV) to α6(IV) chains, by cultured human lung fibroblasts. Consistent with our data are findings that α3 (IV) to α6(IV) chains tended to disappear in acinar and ductal BMs of the labial salivary gland in Sjögren's syndrome 33 and in the BM of several malignant neoplasms, such as bronchioloalveolar carcinoma 18 and gastric carcinoma, 34 but that α1(IV) and α2(IV) chains were expressed continuously in the BM even in those pathologic conditions. Moreover, no reliable report about α3(IV) to α6(IV) chains being produced by cultured fibroblasts in vitro has been published.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, we found that TGF-β1 stimulation, in a dose-dependent manner, increased the production and mRNA expression of α1(IV) and α2(IV) chains, but not α3(IV) to α6(IV) chains, by cultured human lung fibroblasts. Consistent with our data are findings that α3 (IV) to α6(IV) chains tended to disappear in acinar and ductal BMs of the labial salivary gland in Sjögren's syndrome 33 and in the BM of several malignant neoplasms, such as bronchioloalveolar carcinoma 18 and gastric carcinoma, 34 but that α1(IV) and α2(IV) chains were expressed continuously in the BM even in those pathologic conditions. Moreover, no reliable report about α3(IV) to α6(IV) chains being produced by cultured fibroblasts in vitro has been published.…”
Section: Discussionsupporting
confidence: 91%
“…α3(IV), α4(IV), α5 (IV), and α6(IV) chains, however, showed restricted expression: α3(IV) and α4(IV) chains were expressed only in the alveolar BM (Figure 2g, black arrows); the α5(IV) chain was expressed in BMs of alveoli (Figure 2j, black arrows) and smooth muscle cells (arrowheads); and the α6(IV) chain was expressed in BMs of bronchial epithelium and smooth muscle cells (data not shown), in agreement with earlier reports. 18 Early fibrotic lesions of UIP and OP, however, had clear deposits of α1(IV) and α2(IV) chains only in fibroblastic foci of UIP (Figures 2b and e, black stars), not in intraluminal buds of OP (Figures 2c and f, white stars). α1(IV) and α2(IV) chains were present in a fine fibrillar pattern around fibroblasts (white arrows) in fibroblastic foci of UIP (Figure 2b and e, insets).…”
Section: Deposition Of Type I Iii and Iv Collagens And α Chains Of mentioning
confidence: 95%
“…Disruption and altered composition of basement membrane, as detected by laminin-1 and collagen type IV, have been described in cancer cell invasion. [26][27][28] This poses a challenge, however, as staining for laminin-1 and collagen type IV requires extensive proteinase treatment, a procedure, which is rather difficult to standardize. In this context, the evaluation of subepithelial myofibroblast pattern with a-smooth muscle actin staining may provide a relatively easy means to analyze stromal changes in invasive lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ␣3(IV)/␣4(IV)/ ␣5(IV) chains are distributed in the BM of the glomerulus of the kidney and in the BM of the alveoli of the lung, [5][6][7] whereas the [␣5(IV)] 2 /␣6(IV) chains localize in the BM of epidermis, smooth muscle cells, 6 mammary glands, 8 and epithelium of the alimentary tract. 6,9 We have reported the remodeling of type IV collagen ␣ chains in the BM of several invasive cancers, including basal cell carcinoma of the skin, 10 breast cancer, 8 adenocarcinoma of the lung, 11 and adenoid cystic carcinoma of the salivary glands. 12 In the normal colonic epithelium, the BM consists of both the [␣1(IV)] 2 /␣2(IV) and the [␣5(IV)] 2 /␣6(IV) chains, and the loss of the [␣5(IV)] 2 / ␣6(IV) chains in the early invasive stage of colon cancer was observed by immunohistochemical examination.…”
mentioning
confidence: 99%